2019
DOI: 10.1111/aor.13619
|View full text |Cite
|
Sign up to set email alerts
|

Regional citrate anticoagulation for continuous renal replacement therapy in newborns and infants: Focus on citrate accumulation

Abstract: Continuous renal replacement therapy (CRRT) with regional citrate anticoagulation (RCA) in newborns and infants is challenging and accumulation of citrate can occur.There are only a few studies reporting the detailed data on RCA. We aimed to analyze RCA-CRRT at our institution with focus on citrate accumulation. Critically ill newborns and infants up to 11 kg of body weight (BW), treated with RCA-CRRT in the 2011-2016 period were included in this retrospective observational study.Prismaflex(R) and Multifiltrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
1
10
1
Order By: Relevance
“…In this study, there was no significant difference in the incidence of CA before and after the treatment. After RCA-CRRT, the incidence of CA was 14.3%, which was significantly lower than that reported by Persic et al in their study on neonatal and infant RCA-CRRT (25%) ( 14 ). Compared with the NCA group, in the CA group, the body weight was significantly higher and the BFR/BW value was significantly lower, and the molers of citrate per CiFR/BW value was lower but without statistical significance.…”
Section: Discussioncontrasting
confidence: 60%
“…In this study, there was no significant difference in the incidence of CA before and after the treatment. After RCA-CRRT, the incidence of CA was 14.3%, which was significantly lower than that reported by Persic et al in their study on neonatal and infant RCA-CRRT (25%) ( 14 ). Compared with the NCA group, in the CA group, the body weight was significantly higher and the BFR/BW value was significantly lower, and the molers of citrate per CiFR/BW value was lower but without statistical significance.…”
Section: Discussioncontrasting
confidence: 60%
“…Due to smaller vascular access and relatively small blood flows used in neonates, the risk of filter clotting is higher, therefore the need for anticoagulation is equally higher. Contrary to earlier beliefs, recent studies have demonstrated safety and efficacy of RCA in this population [ 12 , 13 ]. In addition, depending on the local expertise and drug availability, standard UFH, LMWH, RCA or argatroban can be safely used in this population.…”
Section: Anticoagulation Strategy In Specific Disease Statesmentioning
confidence: 70%
“…The application of local citrate anticoagulation in CRRT for critically ill patients has received significant attention in recent years because of its unique advantages. Citrate anticoagulation acts by modulating the level of ionized calcium in blood, thus intervening in the coagulation process [14]. After pumping citrate through the arterial end of the CRRT tubing, the ionized calcium in blood binds to citrate radicals to form calcium citrate; this reduces the ionized calcium concentrations in the extracorporeal blood, and affects the conversion of prothrombin to thrombin.…”
Section: Discussionmentioning
confidence: 99%
“…Citrate also affects other coagulation links to maintain the post-filter calcium ion concentration at 0.25-0.35 mmol/L for optimal anticoagulation effect in the extracorporeal circulation [5]. After entering the body, citrate participates in the tricarboxylic acid cycle in the liver, muscle tissue, and renal cortex and is quickly metabolized to bicarbonate radical ions without leaving any residue [4,14]. Supplementation with sufficient ionized calcium to maintain the blood concentration at 1.00-1.20 mmol/L before the blood returns to the body through the venous end restores the coagulation process in the body to normal.…”
Section: Discussionmentioning
confidence: 99%